Calling for comprehensive explorations between soil invertebrates and arbuscular mycorrhizas. (August 2022) - Chen, Qing-Lin; Hu, Hang-Wei; Zhu, Dong; Zhu, Yong-Guan; He, Ji-Zheng
Abstract : Arbuscular mycorrhizal (AM) fungi and soil invertebrates represent a large proportion of total soil biomass and biodiversity and are vital for plant performance, soil structure, and biogeochemical cycling. However, the role of soil invertebrates in AM fungi development remains elusive. In this opinion article, we summarize the ecological importance of AM fungi and soil invertebrates in the plant–soil continuum and highlight the effects of soil invertebrates on AM fungal hyphae development and functioning. In a context of global change, we envision that better mechanistic understanding of the complex feedback via chemical signaling pathways across the interactions between soil invertebrates and AM fungi is critical to predict their ecological consequences and will open new avenues for promoting ecosystem resilience and sustainability. Highlights: Arbuscular mycorrhizal fungi and soil invertebrates play critical roles in maintaining ecosystem primary productivity, nutrient cycling, soil health, and climate regulation. Soil invertebrates may affect the development of arbuscular mycorrhizal fungi through both direct (consumption, incidental damage, and dispersal vectors) and indirect effects (volatile organic compounds and nonvolatile secondary metabolites). Global environmental changes such as warming, drought, land use change, and microplastic pollution may affect the diversity and function of arbuscular mycorrhizal fungi and soil invertebrates. Unravelling the complex interactions between plants and soil biota will allow harnessing the potential of arbuscular mycorrhizal symbioses to improve plant resilience to biotic and abiotic stresses and to increase ecosystem sustainability in the changing environment.